Morphophonology and compensation in Specific Language Impairment: Evidence from Standard Modern Greek and Cypriot Greek. (1st February 2019) - Mastropavlou, Maria; Petinou, Kakia; Tsimpli, Ianthi Maria; Georgiou, Anastasios M.
ABSTRACT: The current study investigates the role of the morphophonological realisation of grammatical features as a compensatory mechanism for morphosyntactic deficits in specific language impairment (SLI). The phenomenon examined is past tense formation in Standard Modern Greek (SMG) and Cypriot Greek (CG) as it manifests a distinction in morphophonological salience realisation in the two linguistic varieties via differential use of a stress shift and stressed syllabic augment [é] required for past tense rule formation. Participants were pre-schoolers with typical language development (TD) and children with SLI. Subjects produced real verb (RV) and pseudo-verb stimuli (PV) in sentence completion tasks. Results indicated that morphophonological properties of past tense formation affected SLI but not TD performance. We attribute the results to the difference in the status of the augment in each variety and the effects it has on its realisation at the phonetic interface. Furthermore, verb contractibility appeared to pose particular difficulties in the performance of all groups.